2020
DOI: 10.1088/2053-1591/ab6f3f
|View full text |Cite
|
Sign up to set email alerts
|

Finite element model based on an efficient layerwise theory for dynamics and active vibration control of smart functionally graded beams

Abstract: In this work, we present a two-noded efficient finite element (FE) model incorporating the layer-wise mechanics for the dynamics and active vibration control of smart functionally graded (FG) beams. The material properties in the FG beam are assumed to vary smoothly in the thickness direction according to power law variation. The effective properties are computed using Mori-Tanaka homogenization scheme. Electric potential profile in the electroded piezoelectric layers/patches is assumed quadratic across its th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Rafiee et al [12] examined thermal bifurcation buckling of CNT reinforced piezoelectric composite beams and concluded that frequency increases with higher CNT volume fraction. Yasin et al [13] performed dynamic study of smart FG beams by FE method using an efficient layer wise theory. They observed splitting of the piezoelectric material surface and the natural frequency is marginally increased for open circuit condition which is not affected in close circuit condition.…”
Section: Introductionmentioning
confidence: 99%
“…Rafiee et al [12] examined thermal bifurcation buckling of CNT reinforced piezoelectric composite beams and concluded that frequency increases with higher CNT volume fraction. Yasin et al [13] performed dynamic study of smart FG beams by FE method using an efficient layer wise theory. They observed splitting of the piezoelectric material surface and the natural frequency is marginally increased for open circuit condition which is not affected in close circuit condition.…”
Section: Introductionmentioning
confidence: 99%
“…Larkin and colleagues [9] used the modified couple stress theory to investigate the impact of small-scale phenomena on the natural frequencies and power density of macro-to nanoscale functionally graded energy harvesters with beam lengths ranging from 62.5 mm to 6.25 m. They found that the natural frequencies and power density of the harvesters were affected by small-scale phenomena. A two-node efficient finite element model combining layerwise mechanics was used by Yasin and colleagues [10] to assess the active vibration stabilization of piezoelectric functionally graded beams. A functionally graded porous piezoelectric sandwich nanobeam reinforced by graphene platelets was investigated by Chen et al [11] using the Euler-Bernoulli beam theory and a differential quadrature technique in order to capture the effect of flexoelectricity on the vibration responses of the nanobeam.…”
Section: Introductionmentioning
confidence: 99%
“…Vodenitcharova and Zhang [11] performed buckling and bending analysis of nanocomposite beam made of single wall CNT. Yasin et al [12] performed dynamic analysis of smart FG beam by FEM using an efficient layer wise theory. They observed that splitting of the piezoelectric material surface increases the natural frequency for open circuit condition but not effective in close circuit condition.…”
Section: Introductionmentioning
confidence: 99%